Some questions of tax control quality improvement - R. R. Arabov (Путеводитель предпринимателя)
In the article problems and questions of tax control improvement in Russia are considered. Wider use of the international standards of tax accounting, a measure for improvement of transfer pricing, introduction in domestic practice of tax monitoring and the tool «motivated opinion is offered. The modes of expanded interaction of tax authorities and taxpayers are considered.